Place‐based loss and resilience among disaster‐affected youth. Issue 7 (8th June 2017) - Scannell, Leila; Cox, Robin S.; Fletcher, Sarah
Abstract: As research on young people's disaster experiences is accumulating, one important yet understudied factor underlying their vulnerability and resilience is their connection to certain places. Youth affected by the 2013 floods in Southern Alberta, Canada, provided photographs of places important to their flood experiences and engaged in peer‐to‐peer interviews to discuss place loss and place‐based strength. Damaged or changed places disrupted youth's reliance on place for activities, resources, social ties, sense of continuity, and a connection to the past. Places provided strength when they offered escape from the postdisaster chaos, enabled youth to contribute to recovery, supported physical and psychological need satisfaction, and symbolized strength, renewal, or hope. These findings demonstrate the relevance of place to youth's disaster experiences and inform future qualitative and quantitative work in this area.